Storm water treatment in a multi-step system compared to a single-step system - Schoeps, Maria (2017)
Urban areas are expanding at an increasing pace around the world as well as surfaces with impervious layers, such as streets and rooftops. Precipitation, melt water and water from human activities, which temporarily flow on these surfaces are defined as storm water. As a result of replacing natural land with hard surfaces, a barrier for natural water infiltration is created and amplitude and volume of water runoff are increased. In addition, dissolved and particulate substances are transported with the water during the runoff on hard surfaces, with risk of contaminating the areas in its path. With concentrated and increased runoff, more particles are released and transported with the water. However, proper and sustainable management of storm water reduces the risk of flooding and contamination of water in urban and rural areas. The choice of storm water system, together with maintenance and monitoring, are of great importance for achieving the desired treatment and handling of storm water. In Sweden, dams are one of the most widely used storm water facility in storm water system. Dams function both as water reservoirs and as treatment facilities for removal of particles. In this study, a storm water system located in an expanding industrial area in Rosersberg was examined. The storm water system has the purpose to treat and delay storm water draining to the nearby valuable stream Verkaån. It is a multi-step system, consisting of a series of dams, which is commonly used in Sweden. However, studies on treatment in multi-step systems are scarce. Therefore, the aim of this study was to examine treatment of pollutants in a multi-step system compared to treatment in a single-step system. Monitoring data of pollutant loads from the multiple-dam storm water system in Rosersberg was compared with pollutant loads as generated from modelling of the system in the storm water software, StormTac. Monitored pollutant loads after treatment in multiple dams in the storm water system were lower than the modelled treatment of multiple dams for eleven out of thirteen substances, and lower than the modelled treatment of a single dam for twelve out of thirteen substances. Treatment effect of pollutants in the storm water system in Rosersberg was higher in multiple dams, than in a single dam, for all modelled pollutant loads except for nitrogen. It could therefore be concluded that a multi-step system treats storm water to a larger extent than a single-step system.